The Influence Of Online Shop Features On Intention To Purchase 1991 Roughneck Industrial Fashion Products On Shopee With Credibility As An Intervening Variable - Sendi Muhammad Dikri; Agus Abdurrahman Drs. M.M (Cita Konsultindo Research Center, 2023)
Information and communication technology development has been accelerating in both developed and developing countries, including Indonesia. The internet is one of the emerging technologies that has altered many facets of human life and daily routines. The usage of internet services has been used in a variety of industries, including the economics, particularly in the sale of products via e-commerce platforms such as Shopee. The purpose of this study is to examine the impact of online shop features on Roughneck Fashion Industry 1991 product purchase intentions using the trustworthiness of online reviews. The research results were evaluated using SEM (Structural Equation Modeling) and AMOS (Analysis of Moment Structures) software, with 219 respondents serving as a sample. According to the study's findings, the reliability of reviews has a considerable impact on consumer purchase intentions. The trustworthiness of the Shopee reviews of 1991 Roughneck Industrial Fashion Product is a key aspect in customer purchasing decisions. Based on the findings and discussion, it is possible to conclude that: (1) review correctness impacts review credibility; (2) review completeness influences review credibility; and (3) review completeness affects review credibility. (1) review correctness impacts review credibility; (2) review completeness influences review credibility; and (3) review completeness affects review credibility. (1) review correctness impacts review credibility; (2) review completeness influences review credibility; and (3) review completeness affects review credibility.